Experimental Study of GFRP Reinforced Concrete Beams With U-Shaped CFRP Grid-Reinforced ECC Stay-in-Place Formwork - Wu, Chang; Su, Yanli; Zhang, Pu; Zhu, Hong; Gao, Danying; Sheikh, Shamim Ahmed (Frontiers in Materials, 2022)
Engineered cementitious composites (ECCs) have ultrahigh toughness and ultrahigh ductility and exhibit pseudostrain hardening behavior under tension. ECCs can be applied as an alternative to concrete in tension zones to delay cracking and improve the durability of structures. In this paper, the flexural performance of glass fiber-reinforced polymer (GFRP)-reinforced concrete beams with U-shaped CFRP grid-reinforced ECC formwork was investigated to achieve the high durability of the composite structures. Five beams were designed, including one reference beam with full concrete, one composite beam with a coupon-shaped ECC permanent formwork at the bottom, and three composite beams with the proposed formwork. The effects of the application of the U-shaped ECC formwork, the formwork types, the application of CFRP grids, and the strength of the ECC were investigated. The test results showed that ECCs were an ideal material to improve the flexural behavior of FRP-reinforced concrete beams. The proposed formwork had a positive effect on crack resistance at the serviceability limit and substantially improved the cracking load by 78.57%-85.71% and the ultimate load by 5.29%-15.71% compared with those of the reference beam. Moreover, the proposed formwork improved the shear stiffness of the composite beam. The addition of CFRP grids improved the tensile strength of the ECC formwork and consequently contributed to the improvement in the load capacity of the composite beams.